Factors influencing sexual behaviour between tourists and tourism employees: A systematic review - Simkhada, Padam P; Sharma, Aditi; van Teijlingen, Edwin R; Beanland, Rachel L (Nepal Journal of Epidemiology, 2016)
Background: Increased travel abroad has a significant impact on the incidence and prevalence of Sexually Transmitted Infections (STIs). Previous reviews have focused on the knowledge, attitudes and behaviour of tourists and acquisition of STIs. Less is known about the impact on tourism operators in countries visited by tourists. The aim of this review is to ascertain factors influencing sexual behaviour between workers in the tourism industry and tourists; exploring the prevalence of sexual behaviour between the two populations, their perceptions of sexual risk while engaging in sexual activities and the knowledge of tourism operators regarding STIs. Methods: A systematic review was conducted. Database searches were performed in Medline/Ovid, EMBASE, Cochrane library and CINAHL for studies published between 2000 and March 2016. Grey literature searches were completed in the NHS database and Google Scholar between 2000 and December 2013. Papers were independently selected by two researchers. Data were extracted and critically appraised using a pre-designed extraction form and adapted CASP checklist. Results: The search identified 1,602 studies and 16 were included after review of the full text. Studies were conducted in nine countries. Findings suggest that STI knowledge, attitude and practice were fairly good among tourists and tourism workers, but there is a need for pre-travel advice for travellers, especially those travelling to low and middle-income countries. Greater importance was given to tourists than to tourism operators and locals interacting with tourists. Studies suggest that as a group both tourist and tourist workers were likely to engage in sexual activities. Overall, both condom use and STI screening were low, among tourists as well as tourism operators. Furthermore, studies reported links between drug and alcohol use and sexual behaviour and risk taking. Conclusion: Although less research appeared to have been conducted among tourism workers than tourists, it does demonstrate the need for education, training and promotion of travel medicine. STI screening, pre-travel advice, travel history in terms of contracting STIs and safe-sex awareness-raising are needed. More and better sexual health education and relevant tourism policies are needed globally.